Urban health and happiness in hutongs and highrises - Sass, Hans-Martin (Array, 2020)
Urban bodies are complex integrated adjustable systems (CIAS), in flexible interaction with their natural, cultural, economic and political biotopes. Small entangled communities such as hutongs, existing in China for over 1000 years, and modern high-rise apartment buildings to a different extent represent more or less healthy and stable communities, based on interpersonal and interfamilial interaction, trust and solidarity, shared interest and involvement in sports, arts, gardening, social and other activities. Urban and other communities are interconnected by common history, narratives and visions, religions and internet cyberspaces. Religions and new internet communities extend beyond the local communities of hutongs, apartment buildings, cities and businesses; they may support or threaten local urban community and coherence.